THE FAMOUS CHOPOGAN OF TAKCHI RESIDENTS OF ALACHOPON - Maxammad Raxmonov Xabibullo o‘g‘li (Journal of Learning on History and Social Sciences, 2024)
In this article, the life of cattle herders of Alachopon village, where the Takchi people of Boysun district of Surkhandarya region live, the life of goatherds, goat breeding, breed types and legal rules are presented. In addition, ethnographic stories related to the life of riders are described